Key Factors in the System of Social Protection in Uzbekistan: Traditions and Modernity - Fayzulla Saidovich, Tolipov; Murat Utepbergenovich, Atamuratov; Fatima Abduraximova, Primova; Dilmira Tuychievna, Kuanisheva; Firuza Shavkatovna, Rakhimova (International Journal of Psychosocial Rehabilitation, 2020)
The article explains the important factors of the social protection system in Uzbekistan and the historical traditions on the basis of modernity. It analyzes the issues of state support for low-income families in the country, their comprehensive support, and social support of large families and socially vulnerable segments of the population based on the local conditions and living standards.